Offizielles Bulletin der Internationalen Arbeiter- und Sozialisten-Konferenz
French ed.: Bulletin officiel de la Conférence internationale ouvrière et socialiste (ZK 16255). - Engl. ed.: Official bulletin of the International Labour and Socialist Conference (ZK 16254).